PREVALENCE OF DEPRESSION IN PRENATAL AND POSTNATAL PERIOD (The Research of Medical Science Review, 2025)
Objective: To assess the prevalence of depression in prenatal and postnatal periods. Methods: A cross-sectional study was conducted with the approval of the Ethical Institutional Review Board against ref. no. TUF/IRB/321/24. Through purposive sampling, a sample of 94 participants that are categorized into prenatal and postnatal patients, 47 participants included for each post-natal and prenatal period were collected from Outpatient Department and Wards of District Headquarter Faisalabad, Allied Hospital Faisalabad and Madinah Teaching Hospital Faisalabad. They were analyzed using Edinburgh Peri/Postnatal Depression Scale and Patient Health Questionnaire. Results: Prevalence of depression in prenatal and post-natal period was 11.59% and 13.02% respectively while Patient Health Questionnaire shows 10.02% for prenatal period and 10.89% for postnatal period. Conclusion: It has been concluded that postnatal periods had more depression as compared to the prenatal period as there were remarkable differences in symptoms and severity of depression in prenatal and postnatal period.